Effects of Astaxanthin from Shrimp Shell on Oxidative Stress and Behavior in Animal Model of Alzheimer’s Disease - Takunrat Taksima; Pennapa Chonpathompikunlert; Morakot Sroyraya; Pilaiwanwadee Hutamekalin; Maruj Limpawattana; Wanwimol Klaypradit (Marine Drugs, 2019)
This study aimed to investigate the effect of astaxanthin (ASX) extracted and ASX powder from shrimp (Litopenaeus vannamei) shells on Wistar rats with Alzheimer’s disease, induced by amyloid-β (1-42) peptides. In this task, the rats were divided into eight groups: (1) Control, (2) sham operate, (3) negative control (vehicle) + Aβ1-42, (4) ASX extract+Aβ1-42, (5) commercial ASX + Aβ1-42, (6) ASX powder + Aβ1-42, (7) blank powder + Aβ1-42, and (8) vitamin E + Aβ1-42. All treatments were orally administrated for 30 days. At 14- and 29-days post injection, animals were observed in behavioral tests. On the 31st day, animals were sacrificed; the hippocampus and cortex were collected. Those two brain areas were then homogenized and stored for biochemical and histological analysis. The results showed that the Aβ1-42 infused group significantly reduced cognitive ability and increased memory loss, as assessed by the Morris water maze test, novel object recognition test, and novel object location test. Moreover, the Aβ1-42 infused group exhibited a deterioration of oxidative markers, including glutathione peroxidase enzymes (GPx), lipid peroxidation (MDA), products of protein oxidation, and superoxide anion in the cortex and the hippocampus. Meanwhile, ASX powder (10 mg/kg body weight) showed a significant reduction in cognitive and memory impairments and oxidative stress which is greater than ASX extract in the same dose of compound or vitamin E (100 mg/kg body weight). Our study indicates the beneficial properties of ASX in alleviation of cognitive functions and reducing neurodegeneration in Wistar rats induced by amyloid-β (1-42) peptides.